If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + c = 4 Solving 3 + c = 4 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + c = 4 + -3 Combine like terms: 3 + -3 = 0 0 + c = 4 + -3 c = 4 + -3 Combine like terms: 4 + -3 = 1 c = 1 Simplifying c = 1
| 14x+30=6x-40 | | 6x-19+11x-22=180 | | 8v-1=2+10(v+12) | | 11b-8=10+8(b+11) | | 5(4-3x)=10 | | -39/6 | | 8=12y-11y | | 11(b+4)+9=9b-11 | | 7x+20=12x-30 | | 4x^3+3y^2+2z=0 | | (x*x)-(19-x)(19-x)=38 | | 52=4(1+3k) | | X^2/(3-x)(2-x)=4 | | 3x-4+2x= | | Bw=11 | | 4x+40=15x-30 | | 3x^2-20+24=0 | | 9h-22=66 | | m^2-2m=8 | | 7.14x+7.14=14.28 | | 1.3+5r=7.4 | | 2.6+2x=48 | | (2y-1)*(1-2y)=0 | | 2=3h+5 | | 4x+7(5x)=10 | | 3=2g+8 | | 3x+4(2x)=25 | | (-2x-1)/x=0 | | 2x+3(x+8)=44 | | 7x-2=10x+8 | | 16x^2+14x+49=52 | | 2t+3(t+2)=4 |